Mortality with hydroxichloroquine and azythromycin use in COVID-19 patients undergoing mechanical ventilation in an intensive care unit in Lima - Fernández Merjildo, Diana (2021)
Objective: To estimate mortality rates associated with hydroxichloroquine and azithromycin use in Covid-19 patients undergoing mechanical ventilation in an intensive care unit in Lima. Material and methods: This is a retrospective analytical cohort. One hundred and five patients with Covid-19 undergoing invasive mechanical ventilation who were admitted with a diagnosis of acute respiratory insufficiency to the intensive care unit of Cayetano Heredia Hospital in Lima during 2020. Results: The overall mortality rate was 38%. Most patients (79%) were male, their mean age was 50 ± 13 years, two thirds (65%) did not have comorbidities; APACHE II and SOFA scores were 12 ± 6 points and 5 ± 3 points, respectively. Thirty percent of all patients received hydroxichloroquine, 32% received azithromycin, and 32% received both drugs. Mortality was significantly higher in those patients who received hydroxichloroquine (p= 0.001), azithromycin (p= 0.03), and the combination of hydroxichloroquine and azithromycin (p= 0.001). However, when a Cox regression analysis was performed, it was evidenced that deceased patients were more likely to have been exposed to hydroxichloroquine (p= 0.001) (HR: 21, CI: 3.4-131.3), but this was not the case with azithromycin (p= 0.22) (HR: 0.43, CI: 0.11-1.6). Conclusion: Mortality in Covid-19 patients undergoing invasive mechanical ventilation was higher in those who received hydroxichloroquine.